Saline fluids play a major role in continental crust formation - Castillo, Paterno R. (Frontiers in Earth Science, 2025)
A new general perspective on the long-standing problem of continental crust formation is presented in this study. Unlike prevailing models for continental crust formation that rely heavily on the behavior of major and trace elements in silicate melts in solidus and subsolidus pressure and temperature conditions, this study emphasizes the additional behavior of almost all elements in hydrothermal fluids in subsolidus and above solidus geochemical reactions at or near the Earth’s surface. Based on the latter concept, post-Archaean continental crust is formed along subduction zones by materials from the mantle wedge fluxed by saline metamorphic fluids released from the hydrothermally altered oceanic slab. Archaean continental crust, on the other hand, is formed atop Archaean “lithospheric blocks” by materials from the mantle and from within the middle to lower section of such blocks fluxed by saline metamorphic fluids released from the hydrothermally altered proto-oceanic crust. Although the two formation processes are different, continental crust has a fairly homogeneous andesitic composition because the respective attendant fluid in either process enriches it with fluid-mobile elements. In sum, the significant role of saline fluids in continental crust formation in present, post-Archaean subduction zones is key to that in the past, within Archaean lithosphere and mantle.